Concise Oxford history of Indian business - Tripathi, Dwijendra (New Delhi, 2007)
What are the roots of modern business practices in India? Ever wondered what forces shaped the way Indian business looks today? This book tells the story of the evolution of Indian business from merchants to service providers, focusing on the principal actors whose exploits made the transition possible. Dwijendra Tripathi, a pioneer in the study of business history in India, provides an engaging account of the business methods and families that makes Indian business what it is today.
Keywords: Indian business